Recurrent Microdeletions at Xq27.3-Xq28 and Male Infertility: A Study in the Czech Population - Chylíková, Blanka; Hrdlička, Ivan; Veselá, Kamila; Řežábek, Karel; Liška, František (PLoS One, 2016)
BACKGROUND: Genetic causes of male infertility are hypothesized to involve multiple types of mutations, from single gene defects to complex chromosome rearrangements. Recently, several recurrent X-chromosome microdeletions (located in subtelomeric region of the long arm) were reported to be associated with male infertility in Spanish and Italian males. The aim of our study was to test their prevalence and infertility association in population of men from the Czech Republic. METHODS: 107 males with pathological sperm evaluation resulting in nonobstructive infertility were compared to 131 males with normal fecundity. X-chromosome microdeletions were assessed by +/- PCR with three primer pairs for each region Xcnv64 (Xq27.3), Xcnv67 (Xq28) and Xcnv69 (Xq28). The latter microdeletion was further characterized by amplification across the deleted region, dividing the deletion into three types; A, B and C. RESULTS: We detected presence of isolated Xcnv64 deletion in 3 patients and 14 controls, and Xcnv69 in 3 patients and 6 controls (1 and 1 patient vs.4 and 1 control for types A and B respectively). There was one control with combined Xcnv64 and Xcnv69 type B deletions, and one patient with combination of Xcnv64 and Xcnv69 type C deletions. The frequency of the deletions was thus not higher in patient compared to control group, Xcnv64 was marginally associated with controls (adjusted Fisher´s exact test P = 0.043), Xcnv69 was not associated (P = 0.452). We excluded presence of more extensive rearrangements in two subjects with combined Xcnv64 and Xcnv69 deletions. There was no Xcnv67 deletion in our cohort. CONCLUSION: In conclusion, the two previously reported X-linked microdeletions (Xcnv64 and Xcnv69) do not seem to confer a significant risk to impaired spermatogenesis in the Czech population. The potential clinical role of the previously reported patient-specific Xcnv67 remains to be determined in a larger study population.
Keywords: mutace; chromozomální delece; dospělí; Phenotype; spermie; Adult; Spermatozoa; lidé; Mutation; Infertility, Male; Male; lidské chromozomy X; Chromosome Deletion; Czech Republic; Chromosomes, Human, X; Česká republika; fenotyp; mužská infertilita; mužské pohlaví; Humans